Family reunification for unaccompanied minors: an exploratory study of practice based experiences of professionals - Kråkenes, Ole Henrik (2017)
The number of unaccompanied minors arriving to Sweden has increased steadily over the latter years, with an exceptional growth in 2015. Although the minors arrive separated from parents or other family members it is recognized that family bonds often still exist. In keeping with international principles of family unity, Swedish law ensures the right to apply for family reunification. The aim of my study has been to explore and analyse the process of family reunification based on the perspectives of my informants. This has been done to identify both obstacles and potential of current practice, which may ultimately provide a better framework for developing this area of work. The research questions have focused on three main aspects; the influence family reunification may have for the youths’ situation, how current practice is experienced and what kind of support professionals provide for the youths. The theoretical framework of my study focuses on different family patterns, social capital and relational social work. The empirical data was collected through a total of 10 semi structured interviews, including 8 professionals and 2 youths. Thematic analysis was used for the interpretation of the collected data. The findings of my study indicates that family reunification leads to an increased responsibility on the youths. In addition, the amount of individualized support for the youth is reduced. This suggests that family reunification involves a transition of care responsibility that may not take into account the specific situation the family is in. Their position as newly arrived immigrants involves adapting to a different society system. While existing literature emphasizes the importance of stable transitions when leaving public care, this demonstrates an obstacle for current practice. Another finding was that professionals found it difficult to prepare the youths for upcoming challenges due to their strong focus and desire of getting their family to Sweden. This may further challenge the professionals’ ability of ensuring a stable transition and positive reunification process. While the professionals reflected upon their own practice, I could identify certain elements that was expressed repeatedly by all informants. This led me to distinguish three typical characteristics of their roles; insufficient role, restrictive role and exceeding role. The first mainly illustrated how the professionals had to relate to external factors they had little influence on. The second characteristic pointed out how they themselves restricted their involvement as a way to maintain the focus of their assigned responsibility. The last role characteristic showed how the professionals at times exceeded their ‘professional’ responsibility in order to provide sufficient support for the youths. The latter appeared to be dependent on the quality of relationship they had established with the youth. From these role characteristics, I could further distinguish two kinds of support provided: professionally motivated and personally motivated. The former points to the potential that exists within a professional role, while the latter illustrates the emotional aspect of human related practice. The experiences shared by the two youths illustrated how both kinds of support are valuable and necessary in their own context.